2006
DOI: 10.1002/smll.200600097
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Microfibers Sheathed with Aligned Carbon Nanotubes: Towards Multidimensional, Multicomponent, and Multifunctional Nanomaterials

Abstract: Multicomponent and multifunctional hybrid structures based on microsized carbon fibers sheathed with aligned carbon nanotubes and their derivatives have been successfully prepared, and have been demonstrated to be an effective means for connecting nanoscale entities to the outside world and to possess interesting electrochemical properties attractive for a wide range of potential applications, including in methanol direct fuel cells and highly sensitive biological and chemical sensors. Judicious modification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 40 publications
2
54
1
Order By: Relevance
“…At high temperature, iron may diffuse into silica, forming iron oxide and an iron-silicon alloy [34,35]. Qu et al [36] has reported similar surface damage caused by the high-temperature pyrolysis of iron phthalocyanine (FePc) on silica-coated carbon fibres. Cross-sections of the damaged surface were prepared by FIB sectioning (Supplementary Information, Figure S1) and studied using TEM (Figure 3d, e).…”
Section: Growth Of Mwcnts On Silica Fibresmentioning
confidence: 99%
“…At high temperature, iron may diffuse into silica, forming iron oxide and an iron-silicon alloy [34,35]. Qu et al [36] has reported similar surface damage caused by the high-temperature pyrolysis of iron phthalocyanine (FePc) on silica-coated carbon fibres. Cross-sections of the damaged surface were prepared by FIB sectioning (Supplementary Information, Figure S1) and studied using TEM (Figure 3d, e).…”
Section: Growth Of Mwcnts On Silica Fibresmentioning
confidence: 99%
“…Due to this, there has been an extensive effort to grow multi-walled nanotubes (MWNT) and nano-fibrillar carbon structures on carbon materials [9 14], with only a few recent studies, however, reporting high density MWNT growth. An alumina layer [9] or an SiO 2 [10] layer between the carbon surface and nanotubes is a necessary component to achieve reasonable growth. Direct growth on carbon surfaces [11 14] results in sparse nanotubes grown with low yields in concert with a surface potentially damaged by the catalyst layer.…”
Section: Introductionmentioning
confidence: 99%
“…This hybrid material shows interesting electrochemical properties that are attractive for a wide range of potential applications, including in methanol direct fuel cells, and highly sensitive biological and chemical sensors. [246] …”
Section: Carbon Chain/cnt Junctionsmentioning
confidence: 97%